The Effect of Benson Relaxation Therapy and Murotal Surah Ar-Rahman on Anxiety in Patients With Diabetes Mellitus in The area of The Holy Ghost Sanctuary - Indah Listiyana Putri; Sukarmin; Heny Siswanti (CV. Inara, 2026)
Diabetes mellitus is a chronic disease that often causes psychological stress, one of which is anxiety. Anxiety in people with diabetes can worsen health conditions and hinder the healing process. Non-pharmacological therapies such as benson relaxation therapy and Surah Ar-Rahman's murotal therapy are suspected to have the potential to lower anxiety levels based on several previous study results. The purpose of this study is to determine the effect of benzon and murottal therapy on the anxiety level of patients with diabetes mellitus. This study uses a quasi-experimental design with a pre test and post test control group design approach in one intervention group. There were 52 respondents, of which each group would get 26 respondents who were selected through purposive sampling techniques. Benson and murotal therapy interventions were given for 7 consecutive days with a duration of 10-15 minutes. Anxiety levels were measured before and after the intervention using the Depression Anxiety and Stress Scale questionnaire with a total of 21 questions. The results and discussion were obtained based on the Sapiro Wilk test and the T-test with the Paired Samples Test. The results of the analysis showed that the relaxation therapy of benson and murotal Surah Ar-Rahman had a significant effect on the anxiety level of Diabetes Mellitus patients in the Kaliwungu Health Center area, with a p-value of 0.001 (p<0.05). Meanwhile, the results of the comparison of the intervention group and the control group were with a p-value of >0.0001. The results of this study strengthen the theory that relaxation and spirituality-based nonpharmacological interventions are able to influence psychological responses, particularly in lowering anxiety levels.